The Prosodic Aspects of Politeness in Instructional Interactions of Elementary School Teachers in Surabaya - Pramujiono, Agung; Nurhadi, Taufik; Nurjati, Nunung; Dian Andanty, Ferra; Widya Hanindita, Amelia (KnE Social Sciences, 2022)
This study aimed to describe the prosodic aspects of politeness in the instructional interactions of elementary school teachers in Surabaya. These prosodic aspects describe the sound intensity, duration, speed and tone. The data were collected using observations at four elementary schools in Surabaya. Data analysis was performed by using Praat acoustic analysis devices and a computer software package for the scientific analysis of speech in phonetics. Based on the results, it can be concluded that the intensity, the speed of sound, and the tone of the prosodic aspects of politeness in the declarative mode of speech had lower averages than the prosodic aspects of politeness in the interrogative and imperative modes of speech. This may be because the declarative mode does not contain the illocutionary directive, while the interrogative and imperative modes do, which affects their use in response to threatening acts. Keywords: prosody characteristics, politeness, teacher instructional interactions